The Distinguished Charge-Trapping Capability of the Memory Device with Al2O3-Cu2O Composite as the Charge Storage Layer - 陆建新 欧欣 蓝学新 曹正义 刘晓杰 卢伟 龚昌杰 徐波 李爱东 夏奕东 殷江 刘治国 (中国物理快报：英文版, 2014)
A memory device Si/Al2O3/Al2O3-Cu2O/Al2O3/Pt is fabricated by using atomic layer deposition and r~magnetron sputtering techniques. The memory device including the composite of Al2O3 and Cu2O as the charge storage layer shows a distinguished charge trapping capability. At a working voltage of ±11 V a memory window of 9.22 V is obtained. The x-ray photoelectron spectroscopic study shows a shoulder from Cu2＋ ions around the peak of Cu1＋ ions. It is suggested that the charge-trapping mechanism should be attributed to the defect states formed by the inter-diffusion at the interface of two oxides.